Scenario analysis loss of heat removal from the spent fuel pool on nuclear power plant - M. T. Hakobyan; A. I. Ksenofontov; S. A. Sargsyan (Глобальная ядерная безопасность)
The spent nuclear fuel storage system is designed to store and cool spent fuel for several years taking into account scheduled reloads and unloading of the entire core accumulated after use in a nuclear reactor. It consists of special pools or containers where spent fuel is placed for temporary storage before final treatment or disposal. These systems provide safe and efficient storage of spent fuel to prevent radioactive material from leaking into the environment and minimize risks to human health and the natural environment. The events that occurred during the Fukushima nuclear disaster on March 11, 2011, underscored the importance of safe storage of spent fuel in the spent fuel storage pool. Storage safety has therefore become a key aspect in this area. This article describes the heat sink loss calculations for the analytical substantiation of the emergency response instructions for the shutdown state of the Armenian NPP power unit No.2 using the RELAP5/Mod3.2 computer code. The initiating event in the event of loss of heat removal from the spent fuel pool is considered. The analysis of nuclear safety in the course of the development of a beyond design basis accident with a long NPP blackout was carried out in relation to the spent fuel pool of a power unit with a reactor plant WWER-440 (project V-270). The radiation consequences are estimated. The article provides calculations of the following accidents to determine the necessary actions of the operator: loss of heat removal from the spent fuel pool without operator action and loss of heat removal from the spent fuel pool from the organizations of subsequent make-up of the spent fuel pool with a boron cleaning pump (2NBO-2). The calculations are based on boundary and initial conditions corresponding to the assumptions of the «better estimate».